Lessons Learned from Hereditary 1, 25-Dihydroxyvitamin D–Resistant Rickets Patients on Vitamin D Functions. Issue 3 (12th January 2021) - Tiosano, Dov; Abrams, Steven A; Weisman, Yoseph
ABSTRACT: We summarize here lessons learned from studies on skeletal and extra-skeletal functions of vitamin D in hereditary 1, 25-dihydroxyvitamin D–resistant rickets (HVDRR) patients with a mutant, nonfunctioning vitamin D receptor (VDR). During childhood, HVDRR patients are dependent on intestinal VDR, demonstrate low intestinal fraction calcium absorption, and have a bone calcium accretion rate that leads to hypocalcemia and rickets. After puberty, there is recovery in intestinal calcium absorption and in bone calcium accretion and structure. HVDRR monocytes and lymphocytes show impairment in the expression of antimicrobial proteins and demonstrate a proinflammatory cytokine profile. However, HVDRR patients do not exhibit increased rates of infections or inflammatory diseases. Vitamin D deficiency is associated with asthmatic exacerbations. Surprisingly, HVDRR patients do not usually develop asthma. They have normal allergic tests and lung functions and are protected against provoked bronchial hyperactivity. HVDRR patients have decreased IL-5 levels in their exhaled breath condensate. Given that IL-5 is a key cytokine in the development of airway inflammation and hyperactivity and that VDR is important for IL-5 generation, it is plausible that low lung IL-5 protects HVDRR patients from asthma. Vitamin D metabolites have suppressive effects on the renin angiotensin system. However, no HVDRR patient showed hypertension or echocardiographic pathology, and their renin angiotensin metabolites were normal. The VDR is expressed throughout the reproductive system, suggesting a role in reproduction. However, the reproductive history of HVDRR patients is normal despite the lack of a normal VDR. HVDRR patients provide a unique opportunity to study the role of the VDR and the role of vitamin D in various human systems.